(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the characteristics of 24-hour diets of women aged 20-49 in some coastal communes of Nam Dinh province. Research subjects and methods: Using descriptive research methods on diets through 24-hour diet interviews on 468 subjects who are women aged 20-49 from December 2020 to December 2021 in the coastal areas of Nam Dinh province. Results: Foods providing protein mainly from meat and meat products 133.2 gr/person/day; fish 78 gr/person/day; eggs 22.1 gr/person/day; milk and products 12.1 gs/person/day; beans 10.3 gr/person/day. Rice is the main food providing carbohydrates, accounting for the majority with 332.3 gr/person/day; cereals, tubers and ripe fruits still account for a low proportion. The average energy intake of the study subjects is 1956.1 ± 437.1 (kcal), the ratio of energy-generating nutrients protein/lipid/glucid is not yet balanced at 17.7/16.6/65.7. The level of meeting the recommended needs of some vitamins and minerals in this study has not yet been achieved, specifically the need for calcium 80.6%, iron 55.9%, zinc 71.3%, vitamin A 39.3%, vitamin B1/1000 kcal (0.57), folate 73%. Conclusions: The 24-hour dietary structure of the subjects in this study is still unreasonable, unbalanced, the imbalance rate and micronutrient response are still high. Therefore, interventions are needed to improve the 24-hour diet of the above group of women.